Pengaruh Kepemimpinan Kepala Sekolah, Iklim Sekolah dan Kompetensi Guru terhadap Mutu Pendidikan di MTS Kabupaten Jeneponto - Budi Susanto; Mattalatta Mattalatta (Pascasarjana STIE Amkop Makassar, 2018)
ABSTRACTThis study aims to ( 1 ) to know the influence of the principal’s leadership on the quality of education at the MTS school in sub-district Tarowang Jeneponto regency ( 2 ) to know effects of climate of the schools to the quality of education in the participants mtsTarowang Jeneponto regency ( 3 ) to know the influence of teacher competencies against the quality of education in the participants MTS Tarowang Jeneponto regency ( 4 ) to know school head ,leadership climate schools and teacher competencies together against the quality of education in the participants at their own MTS Tarowang Jeneponto regency.This research was conducted at MTSschool in Tarowang sub-district of Jeneponto regency from Desember 2017 to Februari 2018. The population of this research was MTS teacher in Tarowang district Jeneponto regency which amounted to 80 people. Through Slovin formula obtained by 66 samples.Sampling technique using probability sampling technique precisely simple random sampling. Data collection method used is expost facto survey method by distributing questionnaire (questionnaire) to the teacher who has been tested validity of its realibility according to research conducted. Data analysis used by using descriptive analysis, T-test and F-testThe research results show that (1) The leadership of the principal has a positive and partially significant effect on the quality of education at the MTS school in sub-district Tarowang Jeneponto regency.(2) The school climate is influential and partially significant to the quality of education in MTS schools in sub-districts Tarowang Jeneponto regency.( 3 ) Teacher competencies is influential and significant to the quality of education at MTS school in sub- district Tarowang Jeneponto regency.( 4 ) school head leadership school climate and teacher competencies influential and significant simultaneously on the quality of education in MTS schools in sub-districts Tarowang Jeneponto regency.Keyword: school head leadership school climate teacher competencies, the quality of education